TRANSFORMATION OF THE MEANING OF THE WORD "DOG" IN THE WIDE COMMUNITY ENVIRONMENT - Siregar, Iskandarsyah; Purnama , Ade Riyan; Xien li , Xu (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The emergence of Generation Z (Gen Z) marks a significant societal shift, as it represents the first cohort to be immersed in the digital age practically from birth. Despite being heralded as "digital natives," indicating familiarity with digital technology, Gen Z's actual digital literacy remains a subject of debate. This generation is characterized by its extensive exposure to the internet and portable digital devices, shaping their worldview and communication patterns. Notably, Gen Z's reliance on electronic devices has led to a decline in traditional activities such as reading books, impacting various cognitive and socio-economic factors including vocabulary development, attention span, academic performance, and future economic productivity. This shift in behavior has not only altered the lifestyle of Gen Z but also influenced language usage and semantic evolution. An intriguing consequence of this digital immersion is the transformation of linguistic conventions, evident in the reinterpretation of commonplace words. Take, for example, the word 'dog,' traditionally defined as a four-legged mammal often kept as a pet for guarding purposes. Within the lexicon of Gen Z, 'dog' has undergone a semantic shift, evolving from a noun to a suffix appended to numerous sentences in their communications. This linguistic phenomenon reflects a broader trend of semantic corruption, where words take on new connotations or functions within contemporary discourse. Understanding the implications of this linguistic evolution is crucial for educators, policymakers, and linguists alike. It not only sheds light on the evolving nature of language in the digital age but also underscores the need to adapt educational and communicative strategies to meet the needs of this digitally influenced generation. By exploring the intricate interplay between technology, language, and societal norms, we can gain valuable insights into the dynamics shaping the linguistic landscape of the 21st century.